Assessing Levels of Depressive Symptoms among Heart Failure Patients at Al-Hussein Teaching Hospital in Sammawa City, Iraq - Hammoddi, Karrar A.; RSachit, Kareem. (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to assess the levels of depressive symptoms among heart failure patients and found the relationship between depressive symptomslevels and socio-demographic of responders. The study Initiated from September 2019 to August 2020), The study design was employed in this research is a descriptive design. The sampling of this study was the purposive sample by 100 heart failure patients was admitting at coronary care unit atAL Hussein teaching hospital in Sammawa city, Iraq. The results of data analysis was employed by Statistical Package for Social Science (SSPS version 24).Study showed that most of heart failure patients had severdepressive symptoms(48 %), moderate(32 %),mild (10%). There is no significant association between depressive symptoms andthe patient’s age, gender, education level, income, occupation, residence, admission frequency, duration of disease , and marital status.